Fat components from precooked "Buchada": an edible goat meat by-product - M. S. Madruga (Ciencia y Tecnología Alimentaria, 2007)
Total fat, phospholipid, cholesterol and fatty acid profile were determined for an edible goat meat by-products,named «Buchada», mainly composed by red and white visceras and blood. Such products, which have a large acceptance inLatin-American countries, appeared as one of the alternatives for a better yield of edible meat goat by-products. Fiveformulations elaborated with visceras and goat blood, all edible meat by-products were analysed. Total fat, total cholesteroland total phospholipids contents were high in the edible goat meat by-products, ranged from 70 to 160 g/kg; 1700 to 1940mg/kg; 70 to 140 mg/kg, respectively. Fatty acids composition showed «buchada» contained mostly stearic acid, oleic acid,palmitic acid, and low levels of unsaturated fatty acids. Since it presents high levels of fat, cholesterol and saturated fattyacids, its consumption must be monitored for people submitted to diet with fat restriction.